Field Survey of Radioactive Cesium Contamination in Concrete After the Fukushima-Daiichi Nuclear Power Station Accident - Igarashi, Go; Osako, Masahiko; Yamada, Kazuo; Takeuchi, Yukio (Journal of Advanced Concrete Technology, 2019)
The Fukushima-Daiichi nuclear power station accident in East Japan in 2011 released radioactive cesium (r-Cs) into the surrounding environment. In addition to the major contamination of soil and vegetation, surrounding concrete structures have also been contaminated. Understanding the contamination characteristics is important for the decontamination or disposal of offsite and onsite concrete structures. However, r-Cs contamination of actual concrete has not been extensively investigated. In this paper, the r-Cs contamination characteristics of actual concrete are introduced on the basis of several field surveys and analysis of concrete samples taken from actual contaminated structures in the Fukushima prefecture. As no dissolution to water was detected, the surface contamination was safely removed by water-jet abrasion. However, in KCl solution, significant dissolution of r-Cs was detected. A contamination depth analysis was performed by quantitative r-Cs concentration mapping based on β-ray radiography using imaging plates. In many cases, such as roadside gutter cover plates, r-Cs was located on the surface without significant penetration into the concrete. However, in cases such as degraded concrete, deeper penetration up to several millimeters deep was observed. In cracked concrete, the r-Cs penetrated at least 10 cm, with the contamination level decreasing one order of magnitude in the first 1 cm.